PTH-110 Long term survival following treatment for hepatocellular carcinoma in patients with hereditary haemochromatosis. (22nd June 2015) - Mcphail, M; Abbott, L; Al-Kadhimi, G; Kane, P; Karani, J; Heaton, N; O'Grady, J; Bomford, A; Suddle, A
Abstract : Introduction: Hepatocellular carcinoma (HCC) rates are higher in patients with hereditary haemochromatosis (HH) compared to other aetiologies. Survival with or without liver transplantation (LT) is often deemed less favourable. Modern mortality rates post LT or following loco-regional therapy (LRT) are not well reported therefore prognostic pessimism may be misplaced. Method: Consecutive patients with HH and HCC diagnosed between 2000 and 2013 at our institution were studied. Patients were offered curative liver transplantation (LT), radiofrequency ablation (RFA) or surgical resection; or, non-curative treatment with trans-arterial chemo-embolization (TACE), sorafenib or symptom control according to performance status and Barcelona Clinic Liver Cancer (BCLC) stage. Patient characteristics recorded at time of first HCC diagnosis included demographics, tumour size and multiplicity, severity of liver disease, serum ferritin (SF, as a proxy for HH treatment) and alphafetoprotein (AFP). The primary end-point was all-cause mortality. Results: Forty-one patients (median (range) age 67(44–78) years, 97% male, MELD 8(5–31)) made up the study cohort with a median follow up of 22(3–126) months. Thirty-six patients had cirrhosis and median SF was 256(27–5718) mg/L and median AFP 29(2–197926) kIU/L. Twenty-seven (66%) patients had solitary tumours, 44% were BCLC stage A, 27% BCLC-B, 10% BCLC-C and 5% BCLC-D. TACE was the commonest LRT choice in 21 (49%) patients. Four patients (9%) underwent surgical resection and RFA was performed in 5 (12%) patients. Fourteen patients (32%) underwent LT. Median survival was 27 (95% CI 17–41) months. Patients with >1 HCC did not have decreased survival compared to those with a single tumour (p = 0.386). Five-year survival for patients receiving curative therapy was 77% (80% for LT, 67% for surgery/RFA), and for those undergoing non-curative therapy 5-year survival was 15% (23% for patients receiving TACE). For BCLC-A patients 5-year survival was 64%, 50% for BCLC-B patients and 9% for BCLC-C/D patients (p = 0.002). On age-adjusted Cox regression survival analysis BCLC-C/D stage was independently associated with poor survival (Hazard Ratio 4.05 (1.29–12.63), p = 0.016) but not serum AFP, SF or the presence of cirrhosis. Conclusion: Patients with HCC in the context of HH can achieve comparable survival rates following curative modalities to those with other aetiologies. The BCLC staging system accurately stratifies survival and excellent 5-year survival is possible following LT in selected patients. Disclosure of interest: None Declared.